Optimization of functional components of the developed planters for high-density cotton - SENTHILKUMAR, T; SANKARANARAYANAN, K; ANNAMALAI, S J K (The Indian Journal of Agricultural Sciences, 2021)
High-density planting of cotton at recommended spacing of 60×10 cm facilitates mechanical harvesting of cotton since the system increases the height of lowest boll. Considering the non-availability and poor penetration of planters in the high-density cotton farms in the country which is tedious and labourious, a study was undertaken to optimize the functional components of the existing five planters so as to enhance availability of the planter for high-density planting of cotton. Observations were taken on intra-row spacing at a strip of 8 m length for each treatment. From the results, it was concluded that the CIAE tractor operated pneumatic planter and CIAE inclined plate planter were the ideal planters among the selected ones for high-density planting system of cotton.